Atomic Fe–N4/C in Flexible Carbon Fiber Membrane as Binder‐Free Air Cathode for Zn–Air Batteries with Stable Cycling over 1000 h. Issue 5 (13th December 2021) - Yang, Leping; Zhang, Xu; Yu, Lingxiao; Hou, Jianhua; Zhou, Zhen; Lv, Ruitao
Abstract: Noble‐metal‐free, durable, and high‐efficiency electrocatalysts for oxygen reduction and evolution reaction (ORR/OER) are vital for rechargeable Zn–air batteries (ZABs). Herein, a flexible and free‐standing carbon fiber membrane immobilized with atomically dispersed Fe–N4 /C catalysts (Fe/SNCFs‐NH3 ) is synthesized and used as air cathode for ZABs. The intertwined fibers with hierarchical nanopores facilitate the gas transportation, electrolyte infiltration and electron transfer. The large specific surface area exposes a high concentration of Fe–N4 /C sites embedded in the carbon matrix. Modulation of local atomic configurations by sulfur doping in Fe/SNCFs‐NH3 catalyst leads to excellent ORR and enhanced OER activities. The as‐synthesized Fe/SNCFs‐NH3 catalyst demonstrates a positive half‐wave potential of 0.89 V and a small Tafel slope of 70.82 mV dec –1, outperforming the commercial Pt/C (0.86 V/94.74 mV dec –1 ) and most reported M–N x /C (M = Fe, Co, Ni) catalysts. Experimental characterizations and theoretical calculations uncover the crucial role of S doping in regulating ORR and OER activities. The liquid‐state ZABs with Fe/SNCFs‐NH3 catalyst as air cathode deliver a large peak power density of 255.84 mW cm –2 and long‐term cycle durability over 1000 h. Solid‐state ZAB shows stable cycling at various flat/bent/flat states, demonstrating great prospects in flexible electronic device applications. Abstract : Flexible and free‐standing carbon membrane with atomically dispersed Fe–N4 /C sites is constructed and used as electrocatalyst for oxygen reduction/evolution reaction. In virtue of the hierarchical porous structures and optimized local atomic configurations, the as‐synthesized noble‐metal‐free membrane as binder‐free air cathode demonstrates a stable cycling over 1000 h for Zn–air battery.